St Paul's epistle to the Colossians and to Philemon a revised text with introductions, notes and dissertations - Lightfoot, Joseph Barber, 1828-1889 (London, UK MacMillan, 1892)
Includes bibliographical references and index.
Donated by the late Thomas C. Denton
Keywords: Bible. N.T. Colossians -- commentaries; Bible. N.T. Philemon -- commentaries